Spirits in your area - Furneaux, Jonathan E. (Brisbane, Qld. : [Jonathan E. Furneaux], 2020)
Spirits In Your Area is an interconnected anthology of urban fantasy stories, mostly set in Australia and Greater Oceania. This collection of stories reimagines classic fairy tales and folk ghost stories in a dark, quirky, and surreal way. It's like The Witcher meets The Castle. -- Publisher.
Title from PDF cover page (viewed on 8 December 2020).
Keywords: Fantasy fiction; Short stories; Fantasy fiction; short stories; Short stories; Electronic books